MITIGASI LEARNING LOSS PASCA PANDEMI COVID-19 MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING BERDIFERENSIASI - Hibban, Muhammad Arkan; Pramono, Didi (Universitas Negeri Malang, 2024)
LEARNING LOSS MITIGATION AFTER THE COVID-19 PANDEMIC THROUGH PROJECT-BASED LEARNING DIFFERENTIATION LEARNING MODELCOVID-19's existence in Indonesia has led to several new issues, particularly in education, one of which is students' learning loss. This study aims to analyze how teachers mitigate learning loss and identify the impact of implementing project-based learning differentiation learning models. The methodology employed in this study takes a qualitative approach, combining primary data sources from interviews and observations along with secondary data from written sources such as books and journal articles. As a validity test for this study, source triangulation with narrative data presentation was used. Changes in learning settings induced by the COVID-19 pandemic have resulted in learning loss in students, thus teachers must act immediately using creative learning models to reduce it. Students receive advantages from implementing this project-based learning differentiation methodology in terms of psychological outcomes. The real impact felt by students such as learning more fun, being motivated in class, and feeling comfortable during the learning process is considered to be able to mitigate the occurrence of learning loss in students at SMAN 11 Semarang.Hadirnya COVID-19 di Indonesia membuat munculnya berbagai permasalah baru, tak terkecuali pada bidang pendidikan dimana terdapat istilah baru pada siswa yaitu learning loss. Penelitian ini bertujuan menganalisis bagaimana guru melakukan mitigasi learning loss dan mengidentifikasi dampak implementasi model pembelajaran project based learning berdiferensiasi. Metode yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif dengan menggunakan sumber data wawancara dan observasi sebagai data primer serta dokumentasi, buku, dan artikel jurnal sebagai data sekunder. Uji validitas penelitian ini menggunakan tiranggulasi sumber dengan penyajian data berupa naratif. Perubahan kondisi belajar karena pandemi COVID-19 kemarin hingga saat ini menimbulkan terjadinya learning loss pada siswa, hingga guru harus bertindak cepat dengan mengimplementasikan model pembelajaran project based learning berdiferensiasi sebagai cara untuk mitigasi terjadinya learning loss pada siswa. Penggunaan model pembelajaran ini menunjukan perubahan psikologi dari siswa. Adanya dampak nyata yang dirasakan oleh siswa seperti belajar lebih menyenangkan, termotivasi dalam pembelajaran di kelas, dan merasa nyaman ketika proses pembelajaran dirasa mampu memitigasi terjadinya learning loss pada siswa di SMAN 11 Semarang.